(untitled) (The Peerian Journal, 2024)
The article deals with the economy and financial history of Kokandd Khanate. In the khanate, the periods of different rulers and the stages of development of the state financial system are analyzed. The connection of the Kokandd khanate with the Bukhara khanate in financial matters is also described